Metaverso y Propiedad Intelectual - León y León, Gustavo (Pontificia Universidad Católica del Perú, 2023)
The idea of the article is to analyze the problems that Intellectual Property must face in the areas of Trademark Law, Inventions and Copyright in the metaverse, that is, in the virtual universe where human beings interact socially and economically as avatars through software in cyberspace. Glimpsing a strong and accelerated raise of the so-called Web3, important companies such as Facebook, Inc., have opted to change their name and direct all their future developments towards the growth of the metaverse that they consider to be the next step in the social connections. However, this virtual universe entails several challenges to Intellectual Property since the legal systems conceived for the physical world cannot always be faithfully adapted to the virtual environment.

La idea del artículo es analizar los problemas que deberá enfrentar la Propiedad Intelectual en los ámbitos del Derecho de Marcas, las Invenciones y los Derechos de Autor en el metaverso, es decir, en el universo virtual donde los seres humanos interactúan social y económicamente como avatares a través de un soporte lógico en el ciberespacio. Vislumbrando un fuerte y acelerado surgimiento de la llamada Web3, empresas tan importantes como Facebook, Inc. han apostado por cambiar su nombre y dirigir todos sus futuros desarrollos hacia el desarrollo del metaverso que consideran es el siguiente paso en las conexiones sociales. Pero este universo virtual entraña varios retos a la Propiedad Intelectual pues los ordenamientos legales concebidos para el mundo físico no siempre se pueden adaptar fielmente al entorno virtual.
Metaverse and Intellectual Property.
Keywords: Intellectual Property; Metaverse; Trademarks; Inventions; Copyrights; Propiedad Intelectual; Metaverso; Marcas; Invenciones; Derechos de Autor; https://purl.org/pe-repo/ocde/ford#5.05.00